The legal status of religion and the administration of Islam in Nigeria and Malaysia - Mokhtar, Khairil Azmin; Oba, Abdulmumini A. (2011)
This paper examines the legal status of religion and the administration of Islam in against the background of the administration of Islamic affairs in Malaysia and Nigeria. Both countries experienced British colonialism. Both countries are Muslim-majority states with substantial non-Muslim populations. Both are based on the concept of modern Muslim states rather than Islamic conception of states. However, there are differences in the legal status of Islam and the administration of affairs of Islam in both countries. In Malaysia, the constitution declares that Islam is the official religion. However this does not mean that Islam is the supreme law of the land or the source of all laws in the country. Rather, the constitutional status of Islam provides the basis for state intervention in, and assistance to, the affairs of Islam. Thus, in Malaysia, there are state institutions charged with administration of various aspects of Islam. In the states where there is a Ruler, the Ruler is also the Head of the religion of Islam in that state. Islamic matters are within the jurisdiction of the state and there are variations in the administration of Islamic affairs across the states in the federation. However, in recent times there have been some successes in the harmonization effort. In Nigeria, there is no official religion. The constitution recognizes religions but the state does not interfere in their administrations. The affairs of Islam in Nigeria are administrated by private bodies outside statutory. The decisions of these bodies do not have the force of law. However, there are Islamic courts administering Islamic law as personal law to all Muslims, and aspects of Islamic muamalat as laws binding between Muslims who so wish. In some states in northern Nigeria, civil courts administer the Shariah Penal Codes as the criminal law binding on Muslims in those states.